(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Age estimation is an integral part of the biological profile employed by forensic anthropologists in order to assist in achieving an identification of an unknown deceased individual. Its estimation is of paramount importance and requires special attention in cases where bodies are found in decomposed, mutilated state or only fragmentary remains are discovered. Material and Method: The present study has been done on post-mortem cases referred to GMERS Medical College, Himmatnagar which is referral center. Very few studies have been conducted on sagittal suture closure in Himmatnagar region . Total 150 post mortem cases were taken and data collected. Result: Present study reveal that Ectocranial obliteration of the various segments of the three main sutures of the skull is so inconclusive that neither does it help in estimating the age of the deceased nor does it provide any supportive evidence in determining the age of skeletal remain. Age was determined on the basis of endocranial suture fusion. Conclusion: It was found that closure of Sagittal suture started in age of 20-29 yrs and closure completed at the age of 61 to 65 yrs.